Wayward son - Rowell, Rainbow (New York : Wednesday Books, 2019)
"THE HOTLY ANTICIPATED SEQUEL TO THE NO. 1 BESTSELLER CARRY ON Simon Snow is back and he's coming to America! The story is supposed to be over. Simon Snow did everything he was supposed to do. He beat the villain. He won the war. He even fell in love. Now comes the good part, right? Now comes the happily ever after... So why can't Simon Snow get off the couch? What he needs, according to his best friend, is a change of scenery. He just needs to see himself in a new light... That's how Simon and Penny and Baz end up in a vintage convertible, tearing across the American West. They find trouble, of course. (Dragons, vampires, skunk-headed things with shotguns.) And they get lost. They get so lost, they start to wonder whether they ever knew where they were headed in the first place... With Wayward Son, Rainbow Rowell has written a book for everyone who ever wondered what happened to the Chosen One after he saved the day. And a book for everyone who was ever more curious about the second kiss than the first. It's another helping of sour cherry scones with an absolutely decadent amount of butter. Come on, Simon Snow. Your hero's journey might be over - but your life has just begun"--